To solve the equation \(3x - 7 - 2x + 5 = 6\), we can follow these steps:
Optional Step:
- Combine like terms on the left side of the equation.
Step 1:
- Combine the \(x\) terms and the constant terms: \(3x - 2x - 7 + 5 = 6\).
Step 2:
- Simplify to get \(x - 2 = 6\).
Step 3:
- Add 2 to both sides to solve for \(x\): \(x = 8\).
So, the complete selection of steps would look like this:
Optional Step: Combine like terms on the left side of the equation. Step 1: Combine the \(x\) terms and constants: \(3x - 2x - 7 + 5 = 6\). Step 2: Simplify to \(x - 2 = 6\). Step 3: Add 2 to both sides: \(x = 8\).